The Role of Sulfur Metabolism in Effective Plant-Microbe Interactions - (:unkn) unknown (My University, 2015)
Bradyrhizobium japonicum USDA110 and Sinorhizobium meliloti RM1021 are nitrogen fixing rhizobia that fix nitrogen when in a symbiotic relationship with legumes. For effective nitrogen-fixing symbiosis to occur these rhizobia must differentiate into nitrogen-fixing bacteroids. This involves the production of high levels of sulfur rich nitrogenase as well as other sulfur containing compounds, creating a large demand for sulfur. This work examined the role of organic sulfur in the establishment of symbiosis and viability of rhizobia in plant nodules. Disruption of the sulfonate sulfur utilization gene ssuD in both Bradyrhizobium japonicum USDA110 and Sinorhizobium meliloti RM1021 resulted in a strong nitrogen deficient phenotype in the host plants. This phenotype was linked to a reduced ability to invade host plants as a result of increased sensitivity to oxidative stress. Additionally, once inside the plant nodules, the ssuD mutants were slow to grow with no observable nitrogen fixation occurring. However, the ability of ssuD mutants to continue to grow at slow rates in nodules resulted in the discovery that sulfate esters are another important sulfur source during symbiosis. Dickeya dadantii 3937 is a phytopathogen, which causes disease in potato, maize, banana, and pineapple as well as ornamental house plants and a wide range of subtropical and tropical plants. D. dadantii has been used as a model organism for the study of secretion systems and virulence factors in phytopathogens. This work examined the regulation, induction, and role of organic and inorganic sulfur utilization genes during the infection of potato by D. dadantii. The regulation of sulfur metabolism in D. dadantii was determined to be similar to the model organism Escherichia coli. However, disruption of the arylsulfatase operon slowed the spread of maceration in potato infections despite D. dadantii being unable to grow on arylsulfonates. Examination of the arylsulfatase operon resulted in the discovery of a phenol dependent sulfotransferase that was able to sulfonate salicylic acid and is hypothesized to play a role in subverting salicylic acid induced immunity in host plants.
Keywords: Bradyrhizobium Japonicum; Dickeya Dadantii; Sinorhizobium Meliloti; Sulfate; Sulfotransferase; Sulfur